Influencia climática sobre la variación radial de caracteres anatómicos de madera en Abies religiosa - Bernal-Salazar, Sergio; Terrazas Salgado, Teresa (Instituto de Ecología, A.C., 2016)
The objective of this research was to characterize radial tracheid variation and to identify the climatic features that affect tracheid variation in Abies religiosa ( H.B.K. ) Schldtl. & Cham.. Twenty trees of Abies religiosa were selected in a population at sierra El Campanario in the state of Michoacan. Wood samples were removed at dbh (1.30 m) and prepared by the standard wood procedure. Four anatomical features of tracheids and ring width were analyzed. Tangential diameter of latewood tracheid and tangential lumen diameter of latewood tracheids, as well as tangential lumen diameter of earlywood tracheids show an increment from pith to vascular cambium. Latewood tracheid wall thickness has a strong increment near the pith, followed by amply fluctuations. Ring width possesses an inverse pattern than wall thickness. Regression analyses show that higher temperatures affect tracheid accumulation and size. These results suggest that maximum temperatures affect Abies religiosa cambial cells.